LITERATURE REVIEW ON THE STRATEGIC POSITION OF MURABAHAH AGREEMENT IN SHARIA FINANCING: - Muhammad Rafi; Ahmad Rezky Adenan; Noor Helmalia Agus; Muhammad Zeini Badaly; Erwan Setyanoor (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
This study aims to examine the strategic position of the murabahah contract in Islamic financing through a literature review approach. Murabahah is one of the most widely used Islamic banking products, as it emphasizes the principles of transparency and fairness, making it an essential instrument in the development of the Islamic financial system. The research method applied is a literature review, analyzing various academic sources, fatwas, regulations, and previous studies that discuss the practice and implications of murabahah contracts. Data were collected through a comprehensive review of relevant literature and then critically and comparatively analyzed. The findings indicate that murabahah plays a dominant role in Islamic financing, both in consumptive financing (such as housing and vehicle purchases) and productive financing (working capital and investment). Its main strengths lie in the clarity of contract structure, transparency of profit margins, and compliance with sharia principles. Furthermore, murabahah is relatively easy to implement, low-risk, and widely accepted by society. In conclusion, murabahah occupies a strategic position in Indonesian Islamic banking because it supports financial system stability, expands access to financing, and contributes to community empowerment and MSME development. Therefore, murabahah can continue to serve as a main pillar in the sustainable growth of the Islamic finance industry.